3D VISIBILITY ANALYSIS IN URBAN ENVIRONMENT – COGNITION RESEARCH BASED ON VGE - T. P. Lin; H. Lin; M. Y. Hu (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
The author in this research attempts to illustrate a measurable relationship between the physical environment and human’s visual perception, including the distance, visual angle impact and visual field (a 3D isovist conception) against human's cognition way, by using a 3D visibility analysis method based on the platform of Virtual Geographic Environment (VGE). The whole project carries out in the CUHK campus (the Chinese University of Hong Kong), by adopting a virtual 3D model of the whole campus and survey in real world. A possible model for the simulation of human cognition in urban spaces is expected to be the output of this research, such as what the human perceive from the environment, how their feelings and behaviours are and how they affect the surrounding world. Kevin Lynch raised 5 elements of urban design in 1960s, which are "vitality, sense, fit, access and control". As the development of urban design, several problems around the human's cognitive and behaviour have come out. Due to the restriction of sensing knowledge in urban spaces, the research among the "sense" and the "fit" of urban design were not quite concerned in recent decades. The geo-spatial cognition field comes into being in 1997 and developed in recent 15 years, which made great effort in way-finding and urban behaviour simulation based on the platform of GIS (geographic information system) or VGE. The platform of VGE is recognized as a proper tool for the analysis of human's perception in urban places, because of its efficient 3D spatial data management and excellent 3D visualization for output result. This article will generally describe the visibility analysis method based on the 3D VGE platform. According to the uncertainty and variety of human perception existed in this research, the author attempts to arrange a survey of observer investigation and validation for the analysis results. Four figures related with space and human’s perception will be mainly concerned in this proposal: openness, permeability, environmental pressure and visibility, and these will also be used as the identification for different type of spaces. Generally, the author is aiming at contributing a possible way to understand the reason of human’s cognition in geo-spatial area, and provides efficient mathematical model between spatial information and visual perception to the related research field.